Answer:
Given: The following system:
4x + y − 2z=18 ......[1]
2x-3y+3z = 21 ......[2]
x-3y=6 ......[3]
we can write equation [3] as;
3y = x-6 ......[4]
Multiply by 3 in equation [1] to both sides of an equation we get,
or
12x+3y-6z=54 ......[5]
Substituting the equation [4] in [2] and [5] we get;
2x-(x-6)+3z=21 or
2x-x+6+3z=21
Simplify:
x+3z=15 .....[6] [combine like terms]
12x+x-6-6z =54
Simplify:
13x-6z=60 ......[7] [Combine like terms]
On Solving equation [6] and [7] simultaneously,
x+3z=15
13x-6z=60
we get the value of x
i.e, x=6
Substitute the value of x in equation x+3z=15 we get
6+3z=15 or
3z=9
Simplify:
z=3
Also, substitute the value of x=6 in equation [3] we get the value of y;
x-3y=6
6-3y=6 or
-3y = 0
Simplify:
y = 0
Therefore, the solution to the system of three linear equation is, (6, 0 , 3)
Answer:
1.08
Step-by-step explanation:Simplify the radical by breaking the radicand up into a product of known factors.
This question is incomplete
Complete Question
In the first half of a basketball game, a player scored 9 points on free throws and then scored a number of 2-point shots. In the second half, the player scored the same number of 3-point shots as the number of 2-point shots scored in the first half. Which expression represents the total number of points the player scored in the game?
a) 2x + 3x + 9
b) 2x + 3 + 9
c) 2x + 3x + 9x
d) 2 + 3x + 9
Answer:
a) 2x + 3x + 9
Step-by-step explanation:
Let the number of points shots a player scores = x
In a free throw, the player scored 9 points = 9
The player also scored a number of 2-point shots = 2x
In the second half, the player scored the same number of 3-point shots as the number of 2-point shots scored in the first half = 3x
The expression represents the total number of points the player scored in the game =
2x + 3x + 9
Answer:
3x +4
Step-by-step explanation:
4 more= 4+
the product of 3 and x = 3 times x
=
4+ 3x
Answer:
D im not sure but i hope its right
Step-by-step explanation: